Integrating virtual reality in environmental and construction research - a case study of a building performance analysis and islamic heritage reconstruction animation - Jahn Kassim, Puteri Shireen (2008)
This paper discusses the research of applying Virtual Reality techniques within an analysis and presentations of the results and visualisation output of an environmental performance analysis was conducted to make an assessment in terms of air flow and temperature with the aim to enhance thermal comfort and predict the outcome in terms of thermal comfort. It also presents the use of virtual reality in digital cultural heritage where the tool can be used to enhance understanding on past historical monuments. In the first case study, the numerical and visual output of the simulation was used as a framework to integrate environmental performance data with a walkthrough of pedestrian walkways in selected areas in Precinct 4 of the Putrajaya Masterplan and an Ecohouse . Hence the paper is divided into two parts i.e an example of how the data or graphical output is integrated with a virtual walkthrough of an environmental performance study, and how VR can be used to enhance understanding on cultural heritage.